GTS-12 adjusted age models for ODP Site 144-872 - Auderset, Alexandra; Moretti, Simone; Taphorn, Björn; Ebner, Pia-Rebecca; Kast, Emma; Wang, Xingchen; Schiebel, Ralf; Sigman, Daniel M; Haug, Gerald H; Martínez-García, Alfredo (In: Auderset, A et al. (2022): Cenozoic foraminifera-bound nitrogen isotope records, TEX86-derived global SST compilation, and GTS-12 adjusted age models from multiple ODP/DSDP sites [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.943130, 2022)
GTS-12 timescale adjusted age models for ODP site 872 with biostratigraphic (foraminifer) datums.
Keywords: age models; Biostratigraphy; Cyclostratigraphy; GTS12; Magnetostratigraphy